Determine the meaning of innocence A study in its terms and limits - Ibrahim Salman Qassem Hashem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Our research, tagged with (Defining innocence , a study in its conditions and limits), deals with the meaning of innocence linguistically and idiomatically, and the meaning of the condition linguistically and idiomatically, and clarifies the limit linguistically and idiomatically. And it shows the limits and course of innocence in the type of charges, and sheds light on the meaning of judgmental suspicion and objective suspicion, and how innocence comes in judgmental suspicion and objective suspicion, and the distinction between doubt in assignment and the one charged with it in objective suspicions, as well as clarifies the meaning of capacity, negation of distress and insurance in terms of punishment, and the role of innocence in eliminating the assignment, with an introduction, conclusion and index of sources.